2012
DOI: 10.1155/2012/391629
|View full text |Cite
|
Sign up to set email alerts
|

New Treatment in Advanced Thyroid Cancer

Abstract: Thyroid cancer is the most common endocrine tumor. Thyroidectomy, radioactive iodine, and TSH suppression represent the standard treatment for differentiated thyroid cancer. Since chemotherapy has been shown to be unsuccessful in case of advanced thyroid carcinomas, the research for new therapies is fundamental. In this paper, we reviewed the recent literature reports (pubmed, medline, EMBASE database, and abstracts published in meeting proceedings) on new treatments in advanced nonmedullary and medullary thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…Thyroid carcinomas are generally poorly responsive to cytotoxic chemotherapy [ 39 42 ], which could be attributed to the presence of intracellular inhibitors of apoptotic signaling cascades. The present study showed that HDAC inhibitors induced pro-apoptotic proteins and reduced anti-apoptotic proteins, producing potent antitumor effects in the two thyroid cancer cell lines studied.…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid carcinomas are generally poorly responsive to cytotoxic chemotherapy [ 39 42 ], which could be attributed to the presence of intracellular inhibitors of apoptotic signaling cascades. The present study showed that HDAC inhibitors induced pro-apoptotic proteins and reduced anti-apoptotic proteins, producing potent antitumor effects in the two thyroid cancer cell lines studied.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced ADC values have been reported for most malignant tumors and are thought to be due to cellular membranes impeding the mobility of water protons [19,20]. In our study, there was a significant difference between the mean ADC value of benign and malignant nodules (P value < 0.0001), the mean ADC of the malignant thyroid nodules (15 nodules) was (0.71 ± 0.15 × 10 -3 mm 2 /s) while that of the benign thyroid nodules (58 nodules) was (1.7 ± 0.12 × 10 -3 mm 2 /s).…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, the scientific community has made significant strides toward a better understanding of the biology of thyroid cancer, and this research has facilitated significant progress in the development of novel and more effective treatment modalities for advanced thyroid cancer [7,8] . Like most endocrine tumors, thyroid tumors are richly vascularized, and initial clinical studies exploited the important role of increased angiogenesis in thyroid cancer [9] .…”
Section: Introductionmentioning
confidence: 99%